Comparative Transcriptome Analysis of Fungal Pathogen Bipolaris maydis to Understand Pathogenicity Behavior on Resistant and Susceptible Non-CMS Maize Genotypes - Meshram, Shweta; Gogoi, Robin; Bashyal, Bishnu Maya; Kumar, Aundy; Mandal, Pranab Kumar; Hossain, Firoz (Frontiers in Microbiology, 2022)
Bipolaris maydis is pathogen of maize which causes maydis leaf blight disease. In India major losses occurs due to B. maydis race “O” pathogen unlike in the world major losses is due to race “T” pathogen. In present study we conducted in planta transcriptomics study of B. maydis race “O” pathogen after infection on non-CMS maize resistant and susceptible genotype by mRNA sequencing to understand the molecular basis of pathogenicity for better management of pathogen. Approx. 23.4 GB mRNA seq data of B. maydis obtained from both resistant and susceptible maize background for fungus. Differentially Expressed Genes (DEGs) analysis of B. maydis in two different genetic background provided clue that majority of highly differentially expressed genes are associated with mitochondrial, cell wall and chitin synthesis, sugar metabolism, peroxidase activity, MAPK activity, Shikimate dehydrogenase. KEGG analysis shows biosynthetic pathway for secondary metabolism, antibiotics, and carbon metabolism of fungus were highly enriched respectively in susceptible background during infection. Previous studies in other host pathogen system suggests that these above genes play vital role in causing disease in their host plants. Our study is probably first transcriptome study of B. maydis race “O” pathogen and provides in-depth insight of pathogenicity on host.